2021
DOI: 10.34007/jns.v1i3.25
|View full text |Cite
|
Sign up to set email alerts
|

KEMAMPUAN BAKTERI ASAM LAKTAT DALAM MENGHAMBAT Salmonella thypii

Abstract: Lactic acid bacteria are known to have the ability to produce antimicrobial compounds known as bacteriocins. This study aims to determine the ability of lactic acid bacteria to inhibit the growth of Salmonella thypii bacteria. In this study, the lactic acid bacteria used were a collection of the Biology Laboratory of the University of Medan Area. Eight types of lactic acid bacterial isolates were used, including IN01, IN02, SF01, SF02, NN01, NN02 SPU01 and SPU04. A confirmation test was carried out on the grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The results of research conducted by [18] showed that LAB can produce bacteriocin compounds that can inhibit the pathogenic bacteria's growth. Bacteriocins are known to have bactericidal and bacteriostatic abilities, namely the ability to remove and reduce the bacteria's growth [19].…”
Section: Resultsmentioning
confidence: 99%
“…The results of research conducted by [18] showed that LAB can produce bacteriocin compounds that can inhibit the pathogenic bacteria's growth. Bacteriocins are known to have bactericidal and bacteriostatic abilities, namely the ability to remove and reduce the bacteria's growth [19].…”
Section: Resultsmentioning
confidence: 99%
“…Based on previous research conducted by Rahmiati & Simanjuntak (2019) Lactobacillus casei bacteria belong to the group of lactic acid bacteria. Lactic acid bacteria have the ability to produce antibacterial compounds commonly called bacteriocins.…”
Section: Discussionmentioning
confidence: 99%